Miscellaneous Objects - Lichtenberger, Achim; Raja, Rubina (Brepols, 2024)
The Decapolis city of Jerash has long attracted attention from travellers and scholars, due both to the longevity of the site and the remarkable finds uncovered during successive phases of excavation that have taken place from 1902 onwards. Between 2011 and 2016, a Danish-German team, led by the universities of Aarhus and Münster, focused their attention on the Northwest Quarter of Jerash — the highest point within the walled city — and this volume is the sixth in a series of books presenting the team’s final results. In this volume, a wide range of miscellaneous items discovered in the Northwest Quarter are presented, ranging from prehistoric lithics to Ottoman pipes. Material finds covered include stone sculpture, utensils, and inscriptions, as well as bone objects, spindle whorls, and bread stamps, while some scientific analyses of jewellery and terracotta figurines complement the studies. These chapters ensure that all finds from the Northwest Quarter — no matter how small — are made available to researchers, with the contributions gathered here offering unique new insights into the material groups from Gerasa, later Jerash, and into the lives of the population of the city from a longue durée perspective.